IMPLEMENTASI PENDEKATAN TARL TINGKATKAN HASIL BELAJAR SURAT RESMI KELAS VII-2 SMP NEGERI 3 PADANGSIDIMPUAN - Milka Daeli; Besinaria Gea; Jihan Septiani Hasan; Regita Ayuni Putri Ginting; Suryati; Tasya Br Ginting Munte (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to examine the effectiveness of the Teaching at the Right Level (TaRL) approach in improving the learning outcomes of class VII-2 students of SMP Negeri 3 Padangsidimpuan on the material of official letter structure. The background of this study is based on the problem of the low level of student learning completion which only reaches 50%. This study uses a quantitative descriptive method with data collection techniques through observation and assignments that are adjusted to the cognitive level of students (very proficient, proficient, and need guidance). The results of the study showed a significant increase in learning outcomes after the implementation of the TaRL approach, where all students achieved completion with a score range of 80–100. These findings indicate that the TaRL approach is effective in adjusting learning to students' abilities and improving the achievement of learning objectives as a whole.